Playing Level and Position Differences in Body Characteristics and Physical Fitness Performance Among Male Team Handball Players - Hermassi, Souhail; Laudner, Kevin; Schwesig, René (Frontiers in Bioengineering and Biotechnology, 2019)
The primary aim of the study was to examine the anthropometric characteristics, as well as the physical performance of professional handball players classified by playing position and competition level. 20 male players (age: 20.4 ± 0.88 years) from the first handball league and 18 male players (age: 21.3 ± 1.61 years) from the second handball league were categorized as backs (8/8), pivots (5/4), and wings (7/6). The following variables were measured in both groups: peak power; vertical squat jump (SJ) and countermovement jump (CMJ); sprint times over 15 and 30 m; handball throwing velocity during the jump shot (JS) and 3 steps shot (T3 step); upper and lower limb muscle volumes; Yo-Yo Intermittent Recovery Test. Anthropometric data revealed significantly (p=0.003, ηp2=0.248) less muscle volume for second league players (3.13 ± 0.29 l) than for first league (3.71 ± 0.82 l). The cross-sectional area for the first league players was also larger (p=0.010, ηp2=0.192). Regarding performance parameters, we found significant (p<0.05 and ηp2>0.20) league differences in five of 15 (33%) performance parameters: running throw (p2=0.285), SJ power (p2=0.670), SJ velocity (p2=0.900), peak upper limb power (p2=0.231) and Yo-Yo-IR 1 (p2=0.348). The second league players showed higher SJ velocity than the first league players (p2=0.900). In contrast, we detected a greater difference in SJ power (p2=0.670) but in favor of the first league players. Pivots were the players with the highest throwing velocity and wings were the fastest (15 m, 30 m sprint), strongest (countermovement jump) and most enduring (Yo-Yo-IR 1) athletes. Backs showed consistently the lowest level throwing velocity and sprint performance (exception: second league). The anthropometric differences between playing levels and playing positions may indicate the advantageous characteristics that the respective position demands, whereas the playing position differences in physical fitness characteristics may indicate training specificity issues that must be addressed cautiously.